Intensitas dan Persentase Serangan Beberapa Penyakit Utama Pada Tanaman Sawit (Elaeis guineensis Jacq.) di Desa Tebing Tinggi Kecamatan Mara Sebo Ulu Kabupaten Batanghari - Yuza Defitri (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research was carried out in smallholder oil palm plantations in Tebing Tinggi Village, Mara Sebo District, Batanghari Regency from March to June 2021. The purpose of the study was to observe the diseases that exist in oil palm plantations, the percentage and intensity of the disease attacks. This study used a survey method with random sampling at 3 locations of smallholder plantations in Tebing Tinggi village, namely 20 sample plants from each garden. Observe all plants and count how many are symptomatic of the disease. Then calculated the percentage and intensity of disease attacks. Samples of diseased plants were taken and wrapped in damp newspapers for identification at the Unbari Basic Laboratory. The results showed that in Tebing Tinggi village, Mara Sebo Ulu district, the highest percentage of Curvularia leaf spot disease caused by the fungus Curvularia sp was found in P2 area at 40%, Drechslera leaf spot disease attack caused by Drechslera sp fungus was highest in P2 land. by 35%, and the highest attack of crown disease (Crown Disease) caused by the fungus Fusarium sp. was found in P3 land by 20%. The intensity of disease attacks found in Tebing Tinggi Village, namely, the intensity of the attack of Curvularia Leaf Spot disease caused by the fungus Curvularia sp in Tebing Tinggi village was 28.75%, the intensity of Drecshlera Leaf Spot disease caused by Drechslera sp fungus was 26.25% and Crown disease crown disease is 6.6%.